2012
DOI: 10.1021/jf204306z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Beer Bitter Acids Regulating Mechanisms of Gastric Acid Secretion

Abstract: Beer, one of the most consumed beverages worldwide, has been shown to stimulate gastric acid secretion. Although organic acids, formed by fermentation of glucose, are known to be stimulants of gastric acid secretion, very little is known about the effects of different types of beer or the active constituents thereof. In the present study, we compared the effects of different beers on mechanisms of gastric acid secretion. To investigate compound-specific effects on mechanisms of gastric acid secretion, organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 35 publications
2
49
1
Order By: Relevance
“…Considering the influence of stomach acidity on consumer decisions, succinic acid can serve as a key indicator for ingestive drinkability. A recent study on the same topic confirmed this by describing succinic acid and additionally malic acid (not maleic acid) as a potential stimulant . These findings contest earlier observations that found no impact of malic acid on gastric acid secretion .…”
Section: Drinkability and Succinic And Malic Acidssupporting
confidence: 71%
See 1 more Smart Citation
“…Considering the influence of stomach acidity on consumer decisions, succinic acid can serve as a key indicator for ingestive drinkability. A recent study on the same topic confirmed this by describing succinic acid and additionally malic acid (not maleic acid) as a potential stimulant . These findings contest earlier observations that found no impact of malic acid on gastric acid secretion .…”
Section: Drinkability and Succinic And Malic Acidssupporting
confidence: 71%
“…Unfortunately, recent studies – showing the same physiological effect for malic acid – were not known at the beginning of this experiment. For this reason the literature review and subsequent design of experiments only focused on succinic acid.…”
Section: Drinkability and Succinic And Malic Acidsmentioning
confidence: 95%
“…There are receptors on the surface of membrane in the wall cell and the combinatorial material of each receptor is carried and combined through the blood flow. Then, H + /K + ATPase activated on the surface of membrane in the nanocyte is released to the stomach and increases the acidity with the medium of transmitter substance in the cell ( Seol, 2006 ; Walker et al ., 2012 ). In order effectively to control the gastric acid output it is adequate to make use of proton pump inhibitors (PPI) directly inhibiting H + /K + ATPase which is at the last stage of gastric acid output rather than histamine receptor inhibitor ( Wallmark et al ., 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also an activator of gastric acid secretion (GAS) (2)(3)(4)(5). Although part of caffeine's effect appears to be mediated by antagonizing adenosine receptors and inhibition of phosphodiesterases (PDEs) (1), the observation that several other bitter-tasting compounds, such as denatonium benzoate (6); hop-derived beer bitter acids; α-, β-, iso-α-acids (7); and catechin and procyanidin B2 (8) cause gastrin release (6) or GAS (7,8) indicates that bitter substance-evoked chemosensory mechanisms may be involved. Chemosensation potentially plays a role at three sites to regulate GAS: (i) bitter substances could excite oral taste cells and mediate their effects through cephalic regulation of gut physiology (9) or (ii) a bitter compound could also act in the gut through induction of gastrin and/or histamine release from enteroendocrine cells and/or (iii) by modulating acid production in GAS-producing parietal cells (10).…”
mentioning
confidence: 99%